2021
DOI: 10.3390/a14110316
|View full text |Cite
|
Sign up to set email alerts
|

Variation Trends of Fractal Dimension in Epileptic EEG Signals

Abstract: Epileptic diseases take EEG as an important basis for clinical judgment, and fractal algorithms were often used to analyze electroencephalography (EEG) signals. However, the variation trends of fractal dimension (D) were opposite in the literature, i.e., both D decreasing and increasing were reported in previous studies during seizure status relative to the normal status, undermining the feasibility of fractal algorithms for EEG analysis to detect epileptic seizures. In this study, two algorithms with high acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Zuo et al [97] found that the linearity of the scaling region increased with the sampling length, and the minimum sampling length was greater for a smooth profile than that for a rough profile. The advantage of scaling region interception to improve accuracy was also found in a fractal analysis of EEG signals [98].…”
Section: Reality Issue For Fractal Analysismentioning
confidence: 81%
“…Zuo et al [97] found that the linearity of the scaling region increased with the sampling length, and the minimum sampling length was greater for a smooth profile than that for a rough profile. The advantage of scaling region interception to improve accuracy was also found in a fractal analysis of EEG signals [98].…”
Section: Reality Issue For Fractal Analysismentioning
confidence: 81%